Using biological traits analysis to investigate ecological functioning of cold-water coral reefs - de Haast, James Andrew (Department of Biological Sciences, 2025)
Cold-water coral reefs are fragile, slow growing systems that are found in all oceans. Past research has focused on the species assemblages found on cold-water coral reefs. The species found on cold-water coral reefs are representative of the species assemblages found in the surrounding waters, with almost no true obligate reef species. No past studies have attempted to determine if biological traits differ on and off the reef, or between reef zones. Norwegian cold-water coral reefs are well-studied; however, the sites that have been identified as likely cold-water coral reefs in South Africa remain under-studied. This thesis leverages the well-documented Norwegian reefs as a means to predict functioning on South African reefs. To this end, the following questions are addressed: 1) does the location of cold-water reefs off the coast of Norway account for variations in species assemblages, 2) are the functional traits on and near cold-water coral reefs related to environmental factors, and 3) does the location of the reef account for variations in trait assemblages? Video transects conducted on coral reefs by the Norwegian habitat mapping program MAREANO (www.Mareano.no) were used to investigate taxonomic and trait differences between nine reef sites off the coast of Norway. The relationships between taxa found at the sites and the environmental conditions were investigated using ordination, specifically, distance-based redundancy analysis (db-RDA). Traits were assigned to each taxon observed using fuzzy coding (0-3). Information for these trait codes was obtained from The Arctic Traits Database, Polytraits, MARLIN, and FishBase. Traits were assigned for 59 taxa that were not included in established trait databases via literature review. The relationships between biological traits and environmental factors were investigated using a combined RLQ fourth-corner method. Additionally, the community-weighted means of traits were investigated using redundancy analysis (RDA). The species assemblages were significantly influenced by the longitude and latitude of the site, in addition to other environmental variables. The result of the RDA performed on community-weighted means indicated that longitude and latitude explained a significant proportion of the variance in biological traits. The burrow dwelling trait was found to be significantly associated with sandy mud and pebble bottom types, and negatively associated with coral substrata. This was the only significant trait association, indicating that cold-water coral reefs might not have a defined trait assemblage associated with the reef structure. However, it could also be indicative of substantial “area of influence” around each reef, since all subsamples were taken within 400m of a cold-water coral reef, and the majority of sites had coral within 100m. More comparative studies between the results of biological trait analyses and sampling methods (video vs grab vs trawl, etc.) are required in order to quantify observation biases in traits as a result of sampling methodology or experimental design. The findings of this thesis support the idea that reefs aggregate local species, offering refuges and benefits, rather than acting as a host to true obligate reef species